Anti-amoebic potential of azole scaffolds and nanoparticles against pathogenic Acanthamoeba - Shweta, W.; Anwar, Ayaz *; Areeba, A.; Sridewi, Nanthini; Khalid, Mohammad *; Yow, Yoon Yen *; Khan, Naveed Ahmed (Elsevier, 2020)
Acanthamoeba spp. are free living amoeba (FLA) which are widely distributed in nature. They are opportunistic parasites and can cause severe infections to the eye, skin and central nervous system. The advances in drug discovery and modifications in the chemotherapeutic agents have shown little improvement in morbidity and mortality rates associated with Acanthamoeba infections. The mechanism-based process of drug discovery depends on the molecular drug targets present in the signaling pathways in the genome. Synthetic libraries provide a platform for broad spectrum of activities due to their desired structural modifications. Azoles, originally a class of synthetic anti-fungal drugs, disrupt the fungal cell membrane by inhibiting the biosynthesis of ergosterol through the inhibition of cytochrome P450 dependent 14α-lanosterol, a key step of the sterol pathway. Acanthamoeba and fungi share the presence of similar sterol intermediate, as ergosterol is also the major endproduct in the sterol biosynthesis in Acanthamoeba. Sterols present in the eukaryotic cell membrane are one of the most essential lipids and exhibit important structural and signaling functions. Therefore, in this review we highlight the importance of specific targeting of ergosterol present in Acanthamoebic membrane by azole compounds for amoebicidal activity. Previously, azoles have also been repurposed to report antimicrobial, antiparasitic and antibacterial properties. Moreover, by loading the azoles into nanoparticles through advanced techniques in nanotechnology, such as physical encapsulation, adsorption, or chemical conjugation, the pharmacokinetics and therapeutic index of the drugs can be significantly improved. The current review proposes an important strategy to target Acanthamoeba using synthetic libraries of azoles and their conjugated nanoparticles for the first time.